Water intake, faecal output and intestinal motility in horses moved from pasture to a stabled management regime with controlled exercise - Williams, Sarah; Horner, J.; Orton, E.; Green, Martin J.; McMullen, Sarah; Mobasheri, Ali; Freeman, S.L. (Wiley, 2014)
Reasons for performing study: A change in management from pasture to stabling is a risk factor for equine colic.